Analysis Of Leadership Style, Motivation And Environment Non-Physical Work On Employee Performance PT Reza Putra Pratama - Fanny Amanda; Muhammad Yalzamul Insan; Siswa Pratama (Yayasan Multidimensi Kreatif, 2025)
The analysis of the study aims to find out whether leadership style, motivation and non-physical work environment affect the performance of PT Reza Putra Pratama employees. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This study uses multiple linear regression analysis. The sample in this study was 40 respondents. Primary data collection uses questionnaires. The results of the study show that leadershiphas a positive and partially significant effect on the performance of PT Reza Putra Pratama employees. Motivation has a positive and partially significant effect on the performance of PT Reza Putra Pratama employees. The non-physical work environment has a positive and significant effect on performance in a partial way. Leadership style, motivation and non-physical work environment have a positive and significant effect simultaneously on the performance of PT Reza Putra Pratama employees.